Teaching grammar using the PPP model - Ortikov, Uktamjon (The Lingua Spectrum, 2024)
This paper reviews the Presentation, Practice, Production (PPP) model in grammar instruction, evaluating its strengths, limitations, and adaptability in modern language classrooms. The PPP model is recognized for its structured approach to teaching grammatical forms, but it has been criticized for its rigid progression and overemphasis on form over communicative meaning. The paper explores how the PPP model can be modified to meet contemporary pedagogical needs, including integrating technology, enhancing communicative tasks, and fostering learner autonomy. By blending the PPP model with other teaching approaches, educators can create a more dynamic, communicative, and learner-centered framework for grammar teaching.